Emotional Expression Of Carly In Max Giwa's And DaniaPasquini's Street Dance Movie (2010): An Individual Psychological Approach - Sari, Ririn Nur Indah, Drs. Abdillah Nugroho, M. Hum, Dr. Phil. Dewi Candraningrum, M.Ed (2013)
This study aims to explore the emotional expression of Carly's in Max Giwa and Dania Pasquini Street Dance Movie. The objective of the research is to analyze the movie based on its structural elements and to analyze the movie based on an individual psychological approach. The researcher applies a qualitative method. In the method, the researcher uses two data sources, namely primary and secondary data sources. The primary data source is Street Dance movie and the secondary data sources are books or any information which support the researcher in analyzing this research. Techniques of the collection data of the study is library research. The technique of the analysis data is descriptive analysis. Based on the analysis, the researcher draws two conclusions: first, based on the structural analysis shows that Street Dance is simple fiction based on portion for structural elements. Second, the individual psychological analysis shows that there is unstable emotion in human self, especially emotional expression.